2006
DOI: 10.1002/ijc.22051
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of the SFRP genes is associated with drinking, smoking and HPV in head and neck squamous cell carcinoma

Abstract: The soluble frizzled receptor protein (SFRP) family encodes antagonists of the WNT pathway, and silencing of these genes, through promoter hypermethylation, leads to constitutive WNT signaling. In bladder cancers, hypermethylation of the SFRP genes occurs more often in current and former smokers and is a strong predictor of poor patient survival. Hence, we examined methylation of these genes in another tobacco-related epithelial cancer, head and neck squamous cell carcinoma (HNSCC), to determine if the pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 44 publications
(52 reference statements)
4
69
0
2
Order By: Relevance
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,33,34,44 In other publications studying overall HNSCC, OPSCC subgroup size ranged from 9% to 80% of the total study population. [29][30][31][32][35][36][37][38][39][40][41][42][43] There was only one study that reported the distribution of average age, nicotine and alcohol consumption between HPV-positive and HPV-negative tumors of which promoter methylation was evaluated. 34 The mean age in HPV-positive tumors was 56.9 compared with 58.4 in HPV-negative tumors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was also shown that HNSCC risk factors (drinking, smoking and HPV) are associated with epigenetic inactivation of genes, such as the SFRP genes. 11 Future experiments will be necessary to further elucidate the role of epigenetic regulation of NEIL1 expression in HNSCC and to verify whether it is a cause or consequence of tumorigenesis. DNA methylation changes might occur early in carcinogenesis and could therefore be used as an early indicator or biomarker in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example in oesophageal SCC, the frequency of ctnnb1 mutations is only 1.1%, but yet 86.4% of oesophageal SCC tumours contain mutated WNT pathway genes (Song, et al 2014), suggesting the mechanisms by which WNT signaling function is peterbed in SCC tumours, are potentially diverse. Epigenetic inactivation of WNT signaling antagonists such as the SFRP genes is not restricted to cSCC, but rather is detected in a variety of other types of SCC tumours, including oral (Paluszczak, et al 2015;Pannone, et al 2010;Sogabe, et al 2008), oesphageal (Kishino, et al 2016;Liu, et al 2011;Meng, et al 2011;Saito, et al 2014;Yang, et al 2012), cervical (Delmas, et al 2011;Siegel, et al 2015) and head & neck (HN) SCCs (Marsit, et al 2006), and thus could represent a universal mechanism of WNT activation in SCC tumours. LGK974, is well-tollerated, potent and highly efficatious in human HNSCC cells (Liu, et al 2013), suggesting it may prove a lead therapeutic in other SCCs where WNT/β-catenin signaling drives carcinogenesis.…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%